Hubungan Paritas, Pengetahuan, Dan Jarak Ke Fasilitas Kesehatan Terhadap Rendahnya Kunjungan Pemeriksaan Kehamilan (ANC) K4 Di PMB Siti Mulyanti Tahun 2022: The Correlation between Parity, Knowledge, and Distance to Health Facilities to Low K4 Pregnancy Examination Visits (ANC) at PMB Siti Mulyanti in 2022 - Khoerunnisa, Fitri (Dohara POAJ, 2022)
Introduction: WHO 2019 MMR 830 per 100,000 live births. The maternal mortality rate in developing countries is 20 times higher than the maternal mortality rate in developed countries, namely 239 per 100,000 live births, while in developed countries it is only 12 per 100,000 live births. One of the efforts to suppress AKI is to carry out regular ANC visits. Lack of irregular ANC visits can be dangerous for pregnant women and their fetuses. Writing this thesis aims to produce publications of scientific output in indexed journals (ISSN) with a research scope of national boundaries. The purpose of this study was to determine the relationship between parity, knowledge, and distance to health facilities with low K4 pregnancy check-up visits (ANC) at PMB Siti Mulyanti in 2022. Methods: The purpose of this study was to determine the relationship between parity, knowledge, and distance to health facilities on the low level of antenatal care visits (ANC) K4 at PMB Siti Mulyanti in 2022. This type of research used quantitative research, using a cross-sectional approach with analytical descriptive methods. The study population was all pregnant women from January-June 2022 totaling 75 and the research sample was as many as 75 respondents with the Total Sampling technique, namely all members of the population were used as research samples. Results: Data collection using questionnaires and data analysis using the chi-square test. From the results of the chi-square test analysis, it shows that if there is a parity relationship with ANC examination visits, p-value = 0,020 with an OR value of 3,455 (1,313-9,088), knowledge with ANC examination visits p-value = 0,001 with an OR value of 6,571 (2,302-18,756) and the distance to health facilities with ANC examination visits p-value = 0.030 with an OR value of 3,435 (1,228-9,606). Discussion: From the results of the chi-square test analysis, it shows that there is a parity relationship with ANC inspection visits p-value = 0,020 with an OR value of 3,455 (1,313-9,088), knowledge with ANC inspection visits p-value = 0,001 with an OR value of 6,571 (2,302-18,756) and distance to health facilities with ANC examination visits p value = 0,030 with an OR value of 3,435 (1,228-9,606). The conclusion from this study is that there is a relationship between parity, knowledge, distance to health facilities, and the low number of K4 pregnancy check-up visits (ANC) at PMB Siti Mulyanti in 2022.